Gingivektomi sebagai Terapi Korektif Kontur Gingiva pada Pasien dengan Malposisi Gigi (Laporan Kasus) - Khoirunisa Ulayya Azizah; Ariyani Faizah (Yayasan Literasi Sains Indonesia, 2026)
Background: Inflammatory gingival enlargement is a periodontal condition often associated with plaque accumulation and can be exacerbated by local factors such as tooth malposition. Chronic inflammatory changes can develop into a fibrotic component that does not fully regress after nonsurgical therapy, necessitating surgical intervention to restore physiological and aesthetic gingival contour. This case report aims to describe the management of gingivectomy as a corrective therapy for gingival contour in a patient with tooth malposition that did not show optimal resolution after initial therapy. Case: A 23-year-old woman presented with gingival enlargement in the anterior mandibular region accompanied by bleeding during toothbrushing. Examination revealed crowding of teeth 33–43, moderate OHI category, plaque index 32%, gingival index 1.2, and pseudopockets with an average depth of 4 mm. Initial therapy, including scaling and root planing and oral hygiene education, resulted in improvement in inflammation, but gingival enlargement persisted. Gingivectomy using the external bevel technique was performed in the area, followed by gingivoplasty and periodontal pack placement. Result: A two-week post-procedure evaluation revealed no gingival enlargement or bleeding on probing, a decrease in probing depth to an average of 2 mm, and significant improvements in hygiene and plaque index. Conclusion: Gingivectomy preceded by early-phase therapy effectively removes excess gingival tissue, reduces pseudopockets, and creates a more physiological gingival contour. Controlling etiologic factors and maintaining oral hygiene play a crucial role in successful therapy.